Penetapan Kadar Na-Siklamat Pada Minuman Serbuk Instan Dan Minuman Kemasan Kaleng Yang Diperdagangkan Di Delitua Dengan Metode Alkalimetri - Parhan, Parhan (Jurnal FARMASIMED (JFM), 2018)
Packaging beverages or soft drinks are non-alcoholic beverages, processed or powdered liquors containing foodstuffs or other additives both natural and synthetic packaged in ready-to-eat packaging. Instant powder drink is one of the fast food beverage products that contain many artificial sweeteners. The most commonly used artificial sweetener is Na-cyclamate. The use of Na-Cyclamate in large doses will cause health problems. The purpose of this research is to know and compare the content of Na-Cyclamate in instant powder drink with beverage of canned packaging traded in Delitua with provisions SNI 01-6993-2004 that is 1000 mg / kg BB. Samples were collected from drink merchants in Delitua who sold instant powder beverages according to qualitative qualitative analysis criteria that aimed to see the Na-Cyclamate content in the sample by using the sedimentation test with BaCl2. Positive samples containing Na-Cyclamate were determined by Alkalimetry. The results showed that 6 samples of instant powdered beverage and canned container beverage contained Na-Cyclamate with content: A (402,2629 mg / kg), B (395.9280 mg / kg), C (405,4303 mg / kg ), D (272.3985 mg / kg), E (269.2311 mg / kg), and F (392.7606 mg / kg). From the data obtained, it is known that the samples A, B, C, D, E and F are safe for consumption, since the Na-Cyclamate content of the sample does not exceed the limits set by SNI 01-6993-2004 based on the food category of 1000 mg / kg. Na-Cyclamate content found in instant powder drink is higher than Na-Cyclamate levels contained in beverage cans packaging.